2001
DOI: 10.1002/1099-0682(200111)2001:11<2719::aid-ejic2719>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the Hydroxycarbonylation of Styrene with Palladium Systems

Abstract: We present a review concerning the mechanism involved in the hydroxycarbonylation of styrene. We discuss the intermediates proposed in the literature, the effect of the acidic medium, the reactivity and kinetics, as well as the results of theoretical calculations on hydroxycarbonylation and related reactions. We have performed an in situ high-pressure NMR [a] Inmaculada del Río (left) received her Ph.D. in 2000 from the University Rovira i Virgili working on mechanistic aspects of hydroformylation and hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 68 publications
(131 reference statements)
1
56
0
Order By: Relevance
“…This mechanism suggests that Pd‐hydride and Pd‐OMe are the active species in the catalytic reaction. On the other hand the Claver group proposed a mechanism for hydroxycarbonylation of styrene using palladium complexes. They found that palladium hydride and palladium acyl species were present, which suggests a catalytic cycle involving palladium hydride, palladium alkyl and palladium acyl intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism suggests that Pd‐hydride and Pd‐OMe are the active species in the catalytic reaction. On the other hand the Claver group proposed a mechanism for hydroxycarbonylation of styrene using palladium complexes. They found that palladium hydride and palladium acyl species were present, which suggests a catalytic cycle involving palladium hydride, palladium alkyl and palladium acyl intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…The production of the Pd -H species from complexes formed in Cycle B was also demonstrated to occur through the β -elimination of an unsaturated ester after alkene insertion. When the substrate is a vinylarene, the branched alkyl intermediate can be stabilized through the formation of π -benzylic species, with the two complexes in equilibrium [44] . The coexistence of these two cycles was suggested to be the origin of the regioselectivity of these reactions, based on steric factors that would favor the linear insertion of styrene into a Pd -hydride bond, whereas the branched insertion of styrene would be favored into a Pd -alkoxycarbonyl bond [45] .…”
Section: Catalytic Cyclementioning
confidence: 99%
“…The use of bidentate ligands generally leads to a greater amount of linear products, whereas catalytic systems bearing monodentate ligands usually favor the formation of the branched products [46] . This difference in regioselectivity was suggested to be due to the ability of monodentate ligands to coordinate to the palladium center in a cis or a trans manner [44] . However, the study of the alcoholysis step, performed varying the bite angle of diphosphines, indicated that cis coordination of the phosphine ligands is required for this step to be effi cient [47] .…”
Section: Catalytic Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Catalysts containing bidentate diphosphine ligands have been more frequently used for this reaction, but they have the disadvantage to produce branched product in low regio-and enantioselectivity, although a few successful examples have been reported recently. [3][4][5][6][7] Several chelating diphosphines have been extensively studied, particularly interesting are those containing metallocenic fragments, for instance, palladium(II) complexes with 1,1-bis(diphenylphosphino)ferrocene (dppf), 1,1-bis(diphenylphosphino) octamethylferrocene (dppomf), 1,1-bis(diphenyl-phosphino)ruthenocene (dppr), and bis(diphenylphosphino)osmocene (dppo) have proven to catalyze the methoxycarbonylation of ethylene and styrene, showing high selectivity to the linear ester. [8][9][10][11][12][13] Gusev et.…”
Section: -Introductionmentioning
confidence: 99%